(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and subclinical characteristics of Haemophilus influenzae (HI) pneumonia and the antibiotic resistance profiles of the causative bacteria at the Children’s Hospital in 2022. Subjects and Methods: A descriptive study was conducted on 162 children aged <15 years treated for community-acquired pneumonia (CAP) with nasopharyngeal cultures positive for HI at the Respiratory Department and Neonatal Department – Hai Phong Children’s Hospital from January 2022 to December 2022. Results: HI-induced CAP predominantly occurred in children under 2 years of age. The clinical and subclinical features were non-specific, primarily manifesting as cough, wheezing, rales, and scattered patchy opacities on chest X-rays. Most HI strains remained susceptible to third-generation cephalosporins, meropenem, piperacillin/tazobactam, and levofloxacin. However, a high proportion of strains showed resistance to antibiotics such as cefuroxime, azithromycin, and co-trimoxazole. Conclusion: The antibiotic susceptibility test results showed that the isolated strains remained sensitive to third-generation cephalosporins, which could serve as reference data in antibiotic selection based on treatment guidelines and local resistance patterns.